Organizational Value and Organizational Commitment on Post 90s in China: From the Generation Gap - et. al., Chao-Lung Lien , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Post-90s refers to Chinese young generation born after 1990. Which employees has become the backbone of enterprise development. They have significant differences from other generations in the way of thinking, behavior and individual values, which greatly affect their organizational commitment and job performance. This paper takes "post-90s" as the research object and the generation gap as the breakthrough point, based on the traditional human resources theory perspective, explores the influencing mechanism and the deep-underlying reason behind the organization value and the organization commitment. Empirical results compare with the staff of other decade from the influence of organizational value, organizational commitment on job performance. This study provides some theoretical and practical reference for improving enterprise performance and puts forward some suggestions on management implications about how to effectively manage post-90s employees from the perspective of enterprise value.